2011
DOI: 10.1007/s00198-011-1834-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and health status with zoledronic acid and generic alendronate—a secondary analysis of the Rapid Onset and Sustained Efficacy (ROSE) study in postmenopausal women with low bone mass

Abstract: There were no significant differences in quality of life between patients receiving zoledronic acid or alendronate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
(48 reference statements)
0
10
0
7
Order By: Relevance
“…[26][27][28] Furthermore, there are studies evaluating questionnaires based on patients' preferences regarding osteoporosis treatment. [29][30][31][32] However, all these tools are exclusively addressed to patients. In the present study, we aimed to develop what is, to the best of our knowledge, the first questionnaire evaluating the factors that influence the physician's decision to initiate, continue or change a regimen for osteoporosis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Furthermore, there are studies evaluating questionnaires based on patients' preferences regarding osteoporosis treatment. [29][30][31][32] However, all these tools are exclusively addressed to patients. In the present study, we aimed to develop what is, to the best of our knowledge, the first questionnaire evaluating the factors that influence the physician's decision to initiate, continue or change a regimen for osteoporosis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…46 Other bene fits, based on low-quality evidence, may include a small reduction in back pain related to past and future vertebral fractures for teriparatide, 47 but there was little to no effect on quality of life for other therapies. [48][49][50][51] There was low to very low quality evidence for very small risks of serious events such as osteonecrosis of the jaw and atypical fractures or delayed healing (estimated at < 1 per 10 000 communitydwelling older people). [52][53][54] It is unclear whether these risks would be higher among long-term care residents.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…The evidence for risk of atrial fibrillation with bisphosphonates 55 and cerebrovascular or cardiovascular events with raloxifene was also of low quality; 56 these results were imprecise and include the possibility of small to no increases in these events. Venous thromboembolism may increase with raloxifene (12 more [95% CI 7 to 19] per 1000), 56 musculoskeletal events may increase with zoledronic acid (146 more [95% CI 125 to 169] per 1000), 48 and serious infections may increase with denosumab (8 more [95% CI 0 to 18] per 1000). 57 Randomized controlled trials and pharmacovigilance for bisphosphonates and raloxifene showed little to no effect of these drugs on serious gastrointestinal events.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…D'après des données probantes de faible qualité, d'autres bienfaits pourraient être associés à ces traitements, comme une légère diminution de la dorsalgie relativement à des fractures vertébrales passées et à venir pour la tériparatide 47 , mais un effet faible, voire inexistant a été constaté quant à la qualité de vie avec d'autres traitements [48][49][50][51] .…”
Section: Résumé Des Données Probantesunclassified